Developing a Structured Forecasting and Policy Analysis System to Support Inflation-Forecast Targeting (IFT) - Laxton, Douglas (IMF Working Papers; Working Paper, 2009)
This paper presents a basic plan for developing a Forecast and Policy Analysis System designed to support an inflation-forecast targeting regime at a central bank. It includes discussion of the development of data management and reporting processes; the creation of a forecast team and the development of human capital; the implementation of a simple model, plus possible extensions; and the management of regular economic projections. We emphasize that it is better to implement simple models earlier and use them well, rather than wait in an attempt to develop an all-encompassing model.